"Time Did Not Fail Me": Analyzing the Epistle to the Hebrews Through it's Use of Temporal Terminology - Shirck, Ryan (Stone-Campbell journal, 2017)
The Epistle to the Hebrews has been subjected to manifold and sundry methodologies in an effort to understand it. To this end, this paper presents a novel approach: literary criticism by way of Bakhtins chronotope. By analyzing the authors understanding and presentation of time through terminology and narrative, a new avenue of Hebrews studies becomes available, with many potential applications.